EFEKTIVITAS PEMBELAJARAN KONTEKSTUAL MODEL PENGAJARAN BERBASIS MASALAH DALAM MENINGKATKAN PRESTASI DAN PENGUASAAN MATERI PELAJARAN IPA - Rastam, Rastam (Jurnal Pembelajaran Prospektif, 2020)
In order to learn something well, we need to listen, see, ask questions about it, and discuss it with others. Not only that, students need to "do it", that is, describe things in their own way, show examples, try to practice skills and do assignments that demand the knowledge they have acquired. This research uses classroom action research in three cycles. Each cycle consists of four stages,namely: Planning, Acting, Observing, and Reflecting. The subject of this research is the fifth grade students of SDN 6 Wonorejo for the 2018/2019 academic year. The data obtained are in the form of formative test results, observation sheets for teaching and learning activities. From the results of the analysis, it was found that student learning achievement had increased from cycle I to cycle III,namely, cycle I (64.00%), cycle II (76.00%), cycle III (88.00%). The conclusion from this research is that problem-based contextual learning can have a positive effect on the learning motivation of Class V SDN 6 Wonorejo students in the 2018/2019 academic year, and this learning model can be used as an alternative to learning science.